Strategic Engineering of Human Resources Development (HRD) to Respond to the Digital Transformation Era in the Context of Business Information Systems - I Dewa Gede Sayang Adi Yadnya; Fitri Devi Lestari Izaak; Abu Muna Almaududi Ausat (Politeknik Ganesha Medan, 2023)
Digital transformation has reshaped the business landscape, compelling organizations to confront new challenges in terms of technology, business processes, and operational models. This research aims to identify and analyze effective strategies in developing human resources to respond to the digital transformation era, particularly in the context of business information systems. The study employs an in-depth review of existing literature through qualitative analysis to gain a comprehensive understanding of the subject, covering the period from 2012 to 2023. The study's findings indicate that in the face of the rapidly evolving digital transformation era, the role of Human Resources (HR) is crucial for organizational success, especially in the context of Business Information Systems. Digital transformation necessitates organizations to adapt and leverage innovative information technology to maintain their competitiveness. Strategic Engineering of Human Resources Development (HRD) becomes an essential foundation for effectively managing these changes. This process involves planning, development, and implementation of strategies to build HR capabilities that can address the challenges of the digital transformation era.